High shear bond strength between zirconia ceramic and resin cement via surface treatment and cleaning - Li Rui; Shi Qing Ma; Zi Hao Liu; Mei Ling Chen; Juan Liu; Jie Wu; Chen Wang; Zhen Liu; Zi Ge Guo; Rui Jie Lu; Ying Cun Sun (Materials Research Express, 2021)
The bonding strength between ceramic and resin is an important property for all-ceramic dental restoration. However, the chemically inert surface of the ceramic generally limits the interaction with the resin and surface contamination, resulting in reduced bonding strength. Therefore, several methods have been used to physically and chemically treat and clean the surface of the ceramic. However, few reports exist regarding long-term bond durability. Herein, we investigate the effect of surface cleaning and multiple treatments on the long-term bonding strength between zirconia and resin cement before and after thermal cycling. The shear bond strength in every group was characterized using a universal mechanical testing machine and averaged from 16 measurements. Results show that after cleaning using Ivoclean with a microbrush, the zirconia surface treated by a mixed silane showed a maximum shear bonding strength of up to 32.5 MPa and retained 29.7 MPa after 5000 thermal cycles. This result indicates that the silanized surface shows excellent bond durability by resisting the damage induced by cyclic expansion and contraction. Long-term high bonding strength arises from combined cleaning and treatment, removing saliva or other organic impurities and forming Si–O–Si and –C–C– at the interface and micromechanical interlocking. This result is promising for future applications in high-strength all-ceramic restoration by optimizing the surface treatment.